Reproducibility of T All-Inside Arthroscopic ATFL Repair With Internal Brace Augmentation: Multicenter Midterm Outcomes in Chronic Lateral Ankle Instability - Araújo Nunes, Gustavo; de Souza Nery, Caio Augusto; Ferraz Ferreira, Gabriel; Zambelli de Almeida Pinto, Roberto; Soares Baumfeld, Daniel; Costa Machado, Paula (Journal of the Foot & Ankle, 2026)
Introduction: Chronic lateral ankle instability (CLAI) may require surgery after failed nonoperative care. We evaluated functional outcomes of a true all-inside arthroscopic anterior talofibular ligament (ATFL) repair augmented with suture tape internal brace, and whether concomitant intra-articular lesions or postoperative stiffness influenced results. Methods: Multicenter retrospective cohort of 51 consecutive CLAI patients treated from March 2021 to September 2023. FAAM, LEFS, MOXFQ and EQ-5D VAS were collected preoperatively and at final follow-up. Paired comparisons used Wilcoxon signed-rank or paired t tests. Subgroup analyses compared patients with/without associated lesions and with/without mild postoperative stiffness. Results: Mean follow-up was 24 months. All scores improved significantly (p<0.001) with large effect sizes: FAAM 32.97±20.98 to 95.57±6.13 (d=2.83); LEFS 44.75±17.21 to 95.95±6.83 (d=2.83); MOXFQ 57.11±20.50 to 96.81±6.04 (d=1.77); EQ-5D VAS 65.39±15.09 to 92.59±9.92 (d=1.45). Patients with concomitant lesions or mild stiffness had slightly lower absolute postoperative scores, but functional gain (Δ) did not differ between subgroups (all p>0.05). No recurrence of instability was observed. Conclusions: True all-inside arthroscopic ATFL repair with internal brace augmentation provides substantial functional improvement, high stability and low complications in CLAI, without clinically relevant compromise from concomitant lesions or mild postoperative stiffness.